Analisis Kualitas Butir Soal Pilihan Ganda pada Mata Pelajaran Konsentrasi Keahlian - Nofiri Gea; Paras Patikasari; Deswita Maharani Padang; Dina Ampera; Untung Desy Purnamasari (Alpatih Harapan Semesta, 2026)
This study aims to analyze the quality of multiple-choice test items. This research employed a descriptive quantitative approach involving 30 students of SMK Negeri 3 Tebing Tinggi as the research subjects. The object of the study consisted of 25 multiple-choice items. The data were collected through tests and documentation, then analyzed quantitatively to determine the quality of each test item. The results of the difficulty level analysis showed that 10 items were difficult, moderate items consisting of 13 items, and 2 easy items. The discrimination index analysis indicated that most items were categorized as very good, with 17 items in this category, while 2 items were categorized as good, 4 items as sufficient, and 2 items as poor. Meanwhile, the distractor effectiveness analysis showed that 17 items had very good distractors, while 8 items required revision due to ineffective answer options. Based on the findings, it can be concluded that item analysis is essential to ensure the quality of evaluation instruments, so that the scoring and assessment of students' learning outcomes can be conducted more objectively, accurately, and fairly